Pengaruh Brand Image, Trust, Perceived Price, dan eWOM terhadap Purchase Intention Smartphone di Jakarta - Deddy Saputra (Universitas Tarumanagara, 2021)
The purpose of this research is to examine the influence of brand image, trust, perceived price and eWOM (electronic word of mouth) towards purchase intention smartphone on Jakarta. The populations are all smartphone user in Jakarta. The samples data number is collected from 220 respondents who lived in Jakarta, and aged between 21-30 years old who has chosen the smartphone.the data collection technique was carried out by distributing the questionnaires online using Google Form through social media (Whatsapp, Line, Instagram and Facebook). This research uses the non-probability sampling method with conveniece sampling technique. Multiple regression analysis is used to analyze research data by using SPSS Version 22 software. The result of this study has showed that brand image, trust, perceived price and eWOM have positive and significant effect on purchase intention smartphone in Jakarta. Tujuan dari penelitian ini adalah untuk menguji pengaruh brand image, trust, perceived price and eWOM (electronic word of mouth) terhadap purchase intention smartphone di Jakarta. Populasinya adalah seluruh pengguna smartphone di Jakarta. Jumlah sampel data dikumpulkan dari 220 responden yang berdomisili di Jakarta, berusia antara 21-30 tahun yang telah memilih smartphone. Teknik pengumpulan data dilakukan dengan menyebarkan kuesioner secara online menggunakan Google Form melalui media sosial (Whatsapp, Line, Instagram dan Facebook). Penelitian ini menggunakan metode non probability sampling dengan teknik convenience sampling. Analisis regresi berganda digunakan untuk menganalisis data penelitian dengan menggunakan software SPSS versi 22. Hasil penelitian ini menunjukkan bahwa brand image, trust, perceived price dan eWOM berpengaruh positif dan signifikan terhadap purchase intentio smartphone di Jakarta.